Effectiveness of Anticipatory Guidance Education in Improving Maternal Knowledge and Practices of Early Mobilization and Safe Infant Carrying - Sinta Inriani Olla; Maria Magdalalena Mue Juwa (Universitas STRADA Indonesia, 2026)
Anticipatory guidance education is a proactive maternal health approach, but evidence on its effectiveness in improving early mobilization and safe infant carrying remains limited in community settings. This study aimed to evaluate the effectiveness of anticipatory guidance education on maternal knowledge and practices of early mobilization and safe infant carrying at Kamboja Integrated Health Post. A quasi-experimental pretest–posttest control group study was conducted among 40 postpartum mothers (n=20 intervention; n=20 control). The intervention group received three anticipatory guidance sessions over two weeks, while the control group received standard education. Data were collected using validated tools and analyzed with paired and independent t-tests (p<0.05). The intervention group showed significant improvements in knowledge (56.2±8.5 to 82.4±6.7) and practices (52.8±9.1 to 79.6±7.2; p<0.001), while no significant changes were observed in the control group. Anticipatory guidance education effectively improves maternal knowledge and practices and should be integrated into community postpartum care.